Changes in Diet Quality of Adults Patients with Type Two Diabetes : Cohort Study of Non-Communicable Diseases Risk Factors - Mahfuzhoh Fadillah Heryanda; Dodik Briawan; Sudikno Sudikno (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
Background: The compliance of Alternate Healthy Eating Index (AHEI) 2010 influences their risk of complications in type two diabetes mellitus (T2DM). In Indonesia, AHEI-2010 has not been widely used in evaluating the diet quality in people after diagnosed T2DM.Objectives: To analyze changes in diet quality of adults patients with T2DM. Methods: This study was analyzed using a secondary data from “Cohort Study of Non-Communicable Diseases Risk Factors” by Indonesian Ministry of Health, on 105 adults newly diagnosed with T2DM. The diagnosis of T2DM was assessed based on the results laboratory tests of fasting blood glucose (FBG) ≥126 mg/dL and 2-hours post-75-g glucose load (2h-PG) ≥200 mg/dL. Dietary intake data was collected twice (at the beginning and the end of monitoring) using a 24-hour recall. The assessment of diet quality uses modified AHEI-2010 USA according to the Indonesians Dietary Guidelines, especially in the portion of the food components. Results: The total score for diet quality was higher at the beginning of monitoring 54.9 than the end of monitoring 53.3 and there was no statistical significance differences (p≥0.05). The total score from diet quality decreased 1.1 points, 53.4% of subjects showed score deterioration (deteriorating diet quality) and 46.7% showed score improvement (improved diet quality). There was a significant differences at the beginning and the end of monitoring only to components score of red/processed meat (p <0.05).Conclusions: Changes in diet quality that deteriorating over time during monitoring, characterized by a decrease in the total score for diet quality.